Jaminan Perlindungan Hukum Konsumen Muslim Atas Produk Halal Perspektif Indonesia dan Dunia - Makmur, Andi Dadi Mashuri; Sabir; Srihandayani, Muspita; Herlina; Sriwahyuningsih; Rahmadillah; Mustaming (Legal Journal of Law, 2024)
The protection of Muslim consumers of halal products as outlined in the Consumer Protection Law No. 8 of 1999, and the halal product safety system for Muslim consumers as outlined in the Halal Product Protection Law No. 33 of 2014. With the regulations on halal product specifications set by the government, business owners can comply with the halal labeling of their products as a fulfillment of the rights of Muslim consumers. Not only in Indonesia, but also for other countries in the world, the issue of halal product standards is a very important issue to pay attention to. Therefore, this study also provides a global perspective. Together with the Indonesian Ulema Council (MUI), the Indonesian Halal Certification Center can strengthen the role of the Halal Product Guarantee Agency (BPJPH) as a halal certification body that can be trusted and recognized internationally